2013
DOI: 10.3892/ijo.2013.2077
|View full text |Cite
|
Sign up to set email alerts
|

Low concentration of metformin induces a p53-dependent senescence in hepatoma cells via activation of the AMPK pathway

Abstract: The induction of senescence for cancer treatment has provoked considerable interest recently. Metformin, a first-line drug for diabetes mellitus type 2, appears to be associated with a lower risk and improved outcomes in hepatocellular carcinoma (HCC). The mechanism involved in function of metformin in HCC is poorly understood. We show that low doses of metformin induced hepatoma cell senescence characterized by accumulation of senescence-associated β-galactosidase activity (SA-β-gal) and the senescence marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 36 publications
3
56
1
Order By: Relevance
“…Yi et al demonstrated that a low concentration of metformin induced p53-dependent senescence in hepatoma cells, whereas higher doses induced apoptotic cell death in these cells. 24 Our observation that metformin administration restrained the growth of xenograft tumors in BALB/c nude mice is in line with a previous report that metformin treatment decreased tumorigenic potential. 25 Further investigation of the mechanisms underlying metformin's antitumor effect in prostate cancer revealed that metformin increased PEDF expression in both prostate cancer cells and tumor tissue.…”
Section: Discussionsupporting
confidence: 92%
“…Yi et al demonstrated that a low concentration of metformin induced p53-dependent senescence in hepatoma cells, whereas higher doses induced apoptotic cell death in these cells. 24 Our observation that metformin administration restrained the growth of xenograft tumors in BALB/c nude mice is in line with a previous report that metformin treatment decreased tumorigenic potential. 25 Further investigation of the mechanisms underlying metformin's antitumor effect in prostate cancer revealed that metformin increased PEDF expression in both prostate cancer cells and tumor tissue.…”
Section: Discussionsupporting
confidence: 92%
“…81 Low concentration of metformin was reported to induce a p53-dependent senescence in HCC cells via activation of the AMPK pathway. 82 Nonetheless, metformin also protected endothelial cells from hyperglycemia-induced senescence in mouse microvascular 83 So, the role of metformin in cell senescence remains unresolved. In addition, metformin can target cancer stem cells.…”
Section: ■ Antineoplastic Actions Of Metforminmentioning
confidence: 99%
“…In addition, the activation of AMPK has been reported to inhibit the growth of different carcinoma cells such as hepatocarcinoma cell HepG2 and colorectal cancer cell SW620 [8,9]. Recent studies find that genetic manipulation of the AMPK upstream activator LKB1 is crucial for hepatoma development and activated AMPK inhibits hepatoma growth by destabilizing p53 in a SIRT1-dependent manner [10]. These findings provide evidence that AMPK may serve as a potential anti-tumor target for treating different carcinomas.…”
Section: Introductionmentioning
confidence: 94%